Analisis Persepsi Mahasiswa FISIP Universitas Brawijaya mengenai Kekerasan Seksual yang Dialami Laki-Laki - Zhafira, Jasmine Eka; Bilahmar, Syifa Sapuro; As-Suvi, Fitra Cantika (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2025)
Public understanding of sexual violence remains limited, with a prevailing tendency to position women as the primary victims, while men are rarely considered as a vulnerable group. This study aims to analyze the perspectives of students from the Faculty of Social and Political Sciences (FISIP) at Universitas Brawijaya regarding cases of sexual violence experienced by men, as well as to examine how social constructions, cultural values, religious teachings, and educational systems shape such perceptions. A descriptive quantitative approach was employed by distributing online questionnaires via Google Forms. The sample was determined using purposive sampling, with the criteria of being active FISIP students who voluntarily and anonymously participated in the study. The findings indicate that most respondents acknowledged that men can also be victims of sexual violence. However, this awareness is often hindered by stereotypes of masculinity, social pressures to always appear strong, and the limited academic discourse on this issue. Conversely, religious and ethical values are perceived as essential moral foundations to support the protection of all victims, regardless of gender. This study highlights the urgency of implementing inclusive and gender-sensitive education to foster a safe, just, and responsive campus environment against all forms of sexual violence.